Tari Ratoeh Duek Perspektif Nilai Estetika Islam - FAKHRUNNISA ALTAS (Universitas Negeri Medan, 2017)
This study aims to find a way of presenting the music as accompaniment in the Sikh religious worship terkhususnya part Asadivaar, music functions as an accompaniment in implementing Asadivaar, and uses musical instruments in worship Asadivaar music as an accompaniment. This study is based on a theoretical foundation to explain the meaning form of presentation, understanding the function, the music, the music instrument, understanding of the Sikhs. This research was conducted at Gurdwara Nanak DevJiKampungKeling Medan in June until August 2016. The method in this research use descriptive qualitative research. Population Board Gurdwara and Sikh People who worship Gudawara Nanak DevJi while samples numbered 20 people. Data collected through observation, interviews, documentation, and literature study. The results of this study indicate that the form of presentation in the rituals of the Sikh religion is particularly Asadivaar implemented during worship takes place. There are four functions of music in the liturgy Asadivaar, namely Disclosure Emotional Function, Communication Function, Aesthetics Appreciation Function, Function and Stability Contribution to Cultural Survival. The usefulness of instrumental music in the worship of the Sikh religion which serves as a Tabla rhythm in the song, Harmonium function as chords and melody in a song, and tambourine serves as tempo and rhythm. Keywords: aesthetics Islam